2022
DOI: 10.9734/psij/2022/v26i130306
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Aquifer Protective Capacity, Against the Surface Contamination. A Case Study of Kaduna Industrial Village, Nigeria

Abstract: Geo-electric soundings was carried out in 22 different locations at Kaduna Refinery Petrochemical Corporation (KRPC) and White Oil and Gas Layout, Mahuta, Kaduna. The aquifer protective capacity and Hydraulic characteristics of the study area was computed from the Geoelectric parameters using Dar-Zarrouk and hydrological parameters. The interpreted data were presented in tabular form, Geoelectric/geology soil profiles and contoured maps. The results show that the study area aquifer is relatively protected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…Though, the noticeable streams around the study area all drain into the famous river Kaduna, while the surface waters are drained directly by evaporation, infiltration, and run-off. However, many researchers are of the view that geological factors such as topography, rain, and erosion can increase the rate at which a dumpsite leaches down the soil to contaminate groundwater [3,4,7,8,16,21]…”
Section: Hydrogeology and Geologymentioning
confidence: 99%
See 4 more Smart Citations
“…Though, the noticeable streams around the study area all drain into the famous river Kaduna, while the surface waters are drained directly by evaporation, infiltration, and run-off. However, many researchers are of the view that geological factors such as topography, rain, and erosion can increase the rate at which a dumpsite leaches down the soil to contaminate groundwater [3,4,7,8,16,21]…”
Section: Hydrogeology and Geologymentioning
confidence: 99%
“…The characteristics of active open dumpsite leachate may be differed, depending on the degradation procedure, hydrological nature, climate conditions and the age of the dumpsite. Many researchers are of the view that environmental pollution and health issues are usually connected to the inadequate treatment of dumpsite leachate [3][4][5], while [6][7][8], believe that the degree of groundwater pollution is a function of hydraulic conductivity at waste dumpsites. Recent studies have shown that the deposited wastes on landfills undergo a series of chemical reactions and changes and the shallow sediments above the water-bearing unit (water table) can get contaminated through leaching of leachates thereby contaminating usable surface water and groundwater resources [1,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations